Supervision of lost pension accounts and unclaimed benefits. Issue 3 (8th July 2019) - Park, Kyoung Gook; Stańko, Dariusz; McShane, Darren
Abstract : Purpose: The purpose of this paper is to investigate how private pension supervisors in selected jurisdictions monitor and address lost pension accounts and unclaimed pension assets or benefits and draw supervisory implications. Design/methodology/approach: This paper is based on the survey on private pension schemes of selected International Organisation of Pension Supervisors member jurisdictions. Findings: This paper finds that there are differences in severity of the issue of lost pension accounts and unclaimed pension benefits among jurisdictions, and that pension supervisors/regulators differ with regard to awareness of and approaches taken to handle this issue. Some jurisdictions show a well-established systematic approach to deal effectively with the problem of lost pension accounts or unclaimed benefits, while other jurisdictions are yet to recognise and tackle the issue. Originality/value: To the best of the authors' knowledge, this is the first larger cross-country study on lost pension accounts and unclaimed benefits in private pension schemes. The paper presents international comparison of this issue in 32 different jurisdictions and provides examples of good supervisory or regulatory practices.